1996
DOI: 10.1111/j.1469-7998.1996.tb05485.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hatching date on parental care, chick growth, and chick mortality in the chinstrap penguin Pygoscelis antarctica

Abstract: We studied the effect of hatching date on breeding performance (chick growth and mortality) and phenology (creching and fledging ages) of the chinstrap penguin during three years. The year affected every variable considered, probably due to pack‐ice persistence and food availability differences between years. Hatching date had slight or no effect on mortality and early growth, but was negatively correlated with creching age, which, in turn, was positively related to final size. The decision to leave the chicks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 12 publications
1
36
0
Order By: Relevance
“…Thus, early-hatched chicks demonstrated a better growth performance. This pattern of association between an early hatching date and a faster chick growth has been repeatedly observed for the chinstrap penguin at the Vapour Col colony in several breeding periods ( /1994( : VinÄ uela et al 19961994: Moreno et al 1997. This fact suggests the existence of important`q uality'' di erences between late-and early-hatching pairs, supporting our analysis design controlling for the hatching date in this non-manipulative study of the effects of egg size on chick growth.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Thus, early-hatched chicks demonstrated a better growth performance. This pattern of association between an early hatching date and a faster chick growth has been repeatedly observed for the chinstrap penguin at the Vapour Col colony in several breeding periods ( /1994( : VinÄ uela et al 19961994: Moreno et al 1997. This fact suggests the existence of important`q uality'' di erences between late-and early-hatching pairs, supporting our analysis design controlling for the hatching date in this non-manipulative study of the effects of egg size on chick growth.…”
Section: Discussionsupporting
confidence: 67%
“…Hatching date has usually been related to parental quality and environmental stress (e.g., weather harshness, food availability) and it has a strong e ect on o spring survival (Daan et al 1988). Based on prior studies with this species where hatching date is negatively associated with chick growth and survival (Moreno et al 1994;VinÄ uela et al 1996;Moreno et al 1997), we analyse the in¯uence of egg size controlling for the e ect of hatching date. We also try to partition the variance in chick growth into those components related to egg size and hatching date to show their relative importance under natural non-manipulative conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We found that early breeders had symptoms of a better health than late breeders as evidenced by lower numbers of lymphocytes and heterophils and higher levels of T-cell-mediated immunocompetence. Breeding date has important implications for reproductive success in this population (Viñuela et al, 1996). Thus immunocompetence may assist us in identifying early and therefore successful breeders in this population.…”
Section: How Can Parental Quality Be Measured?mentioning
confidence: 99%
“…Brood sex ratios and nest size were estimated in a large subcolony (aggregates of nests separated from other such aggregates by areas unused for nesting) of 1,000 nests. Only nests with the modal clutch size of two eggs (Vinuela et al 1996) were considered. Both chicks were sampled for sexing (see below) before mortality occurred (2-6 days after hatching).…”
Section: Study Area and Penguin Samplingmentioning
confidence: 99%
“…(3) Breeding time is a life-history trait profoundly affecting breeding success in birds (Price et al 1988). Chinstrap penguins are no exception, as earlier breeders produce larger and healthier chicks than late breeders (Vinuela et al 1996;Moreno et al 1997). …”
Section: Introductionmentioning
confidence: 99%